2021
DOI: 10.1101/2021.03.02.433576
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathogenic LRRK2 control of primary cilia and Hedgehog signaling in neurons and astrocytes of mouse brain

Abstract: Previously, we showed that cholinergic interneurons of the dorsal striatum lose cilia in mice harboring the Parkinson's-disease associated, kinase activating, R1441C LRRK2 mutation (Dhekne et al., 2018). Here we show that this phenotype is also seen in two mouse strains carrying the most common human G2019S LRRK2 mutation. Heterozygous loss of the PPM1H phosphatase that is specific for LRRK2-phosphorylated Rab GTPases (Berndsen et al., 2019) yields the same cilia loss phenotype, strongly supporting a connectio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 62 publications
3
17
0
Order By: Relevance
“…Moreover, a point mutation in vps35 (vps35-D620N) which causes autosomal-dominant PD (17)(18)(19) and activates the LRRK2 kinase (20) causes a pronounced centrosomal cohesion deficit. Knockout of PPM1H, the phosphatase specific for LRRK2-phosphorylated Rab proteins (21) impairs centrosomal cohesion in the presence of LRRK2 expression, and a recent study shows that heterozygous loss of the PPM1H phosphatase impairs ciliogenesis in the intact mouse brain (38). These data provide strong evidence for the importance of the LRRK2 kinase activity in regulating both ciliogenesis and centrosomal cohesion deficits in non-dividing and dividing cells, respectively.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, a point mutation in vps35 (vps35-D620N) which causes autosomal-dominant PD (17)(18)(19) and activates the LRRK2 kinase (20) causes a pronounced centrosomal cohesion deficit. Knockout of PPM1H, the phosphatase specific for LRRK2-phosphorylated Rab proteins (21) impairs centrosomal cohesion in the presence of LRRK2 expression, and a recent study shows that heterozygous loss of the PPM1H phosphatase impairs ciliogenesis in the intact mouse brain (38). These data provide strong evidence for the importance of the LRRK2 kinase activity in regulating both ciliogenesis and centrosomal cohesion deficits in non-dividing and dividing cells, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…Pathogenic LRRK2 activity causes loss of primary cilia in various cell types in vitro, and the intact brain of G2019S or R1441C LRRK2 knockin mice in vivo (9,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RILPL1 is a poorly characterized protein which regulates ciliogenesis [ 88 ]. The binding of phospho-Rab8/10 to centrosome-localized RILPL1 causes a decrease in primary ciliogenesis in various cell types in vitro as well as in the intact mouse brain [ 72 , 83 , 84 , 89 ], which is at least in part due to the impaired centrosomal recruitment of tau tubulin kinase 2 (TTBK2), a step essential for ciliogenesis initiation [ 90 , 91 ]. We have shown that apart from ciliogenesis, the same phospho-Rab8/10-RILPL1 interaction also causes centrosomal cohesion deficits in dividing cells including in patient-derived peripheral cells [ 77 , 82 , 83 ].…”
Section: Rab Proteins As Lrrk2 Kinase Substratesmentioning
confidence: 99%
“…Whilst it is established that the centrosomal cohesion and ciliogenesis deficits are a direct consequence of enhanced LRRK2 kinase activity and are mediated by the centrosomal accumulation of phospho-Rab8/10 bound to RILPL1, the pathophysiological significance of those alterations remains unclear. One postulated mechanism relates to the observation of ciliary deficits in cholinergic neurons in the striatum, which is expected to disrupt their ability to send neuroprotective signals back to dopaminergic neurons in the substantia nigra [ 84 , 92 ], but other cell-autonomous and non cell-autonomous mechanism(s) are possible as well [ 89 ].…”
Section: Rab Proteins As Lrrk2 Kinase Substratesmentioning
confidence: 99%